A Social Ecological Analysis of Barriers to Weight-loss Success in the Veterans’ Health Administration MOVE! Program - Warner, Jeffrey (My University, 2013)
Veterans receiving healthcare at Veterans Administration (VA) facilities have free access to a multi-level weight loss program called MOVE! MOVE is an acronym for Managing Overweight/Obesity in Veterans Everywhere. Although the program is effective, it is only utilized and completed by about 8% of those who qualify. Like the non-veteran population, obesity is becoming a major health crisis in the veteran population. This capstone project will focus on increasing the usage of the MOVE! program at the Topeka, Kansas VA medical center. The first goal of this project is to increase program awareness among the VA primary care medical staff, which should lead to an increase in patient referrals. The second goal is to improve participant compliance rates once in the program. The third goal is to expand access to MOVE! by working with the VA Women’s Health Department to establish a female-only MOVE! program. MOVE! is an eight week program so this project will encompass three full cycles of classes. Evaluation will be based on the limited data obtained by comparing the first two MOVE! cycles with the cycle immediately preceding my involvement, and analyzing relevant trends in new attendees, number of classes attended per participant, and average weight lost by participants during each cycle. Correlations between program compliance, defined by the number of classes completed, and average weight lost will also be analyzed. The veteran population is similar in many aspects to the general population. Because the MOVE! program is only available to veterans receiving care at VA facilities, the subset of veterans receiving care outside of the VA will not be considered in this project. At the end of fiscal year 2011, about 8,570,000 individuals were enrolled in the VA Health System. This accounts for approximately one third of the entire veteran population. These individuals are predominately male (91.9%), white (79.9%) and have a median age of 60. The largest segment of this population served during the Vietnam era but the fastest growing segment of the population are between the ages of 20 and 29 and have served in Iraq and/or Afghanistan. As a population, veterans have higher annual incomes than the general population and they also have lower rates of unemployment. These statistics can be misleading due to the higher percentage of males in the veteran population and the income disparities between males and females though (www.va.gov/vetdata). In 2010, 92% of military veterans had a high school diploma and 26% had at least a bachelor’s degree, compared to the general population at 86% and 28%, respectively (www.census.gov). Veterans also have significantly higher home ownership rates than the general population, 82% vs. 67% respectively (www.census.gov). The Colmery-O’Neil VA Medical Center in Topeka, KS serves approximately 37,020 veterans, of which about 12,500 are obese. Currently, about 875 referrals have been made to the MOVE! program since its inception in 2006, but actual participation is significantly less. This practicum will address ways to increase the number of participants referred to MOVE!. It will also attempt to remove barriers to participation, and will attempt to increase patient compliance with the program.
Keywords: Public Health; MOVE!; Weight-Loss; Public Health (0573)